EDUWISATA AKUAKULTUR TERINTEGRASI DI UNDANA FARM UNTUK MENDUKUNG KETAHANAN PANGAN DAN KONSUMSI IKAN - Wesly Pasaribu; Yuliana Salosso; I Nyoman Widiarta Mahayasa; Asriati Djonu; Immaria Fransira (Jurnal Abdi Insani, 2026)
Kupang is a semi-arid region that faces challenges related to limited access to nutritious food, vulnerability to climate change, and low diversification of animal protein sources. Under these conditions, the development of an adaptive and educational local food security model becomes important. Undana Farm, as an agro-tourism area in dryland conditions, has the potential to be developed not only as a recreational site but also as a learning medium for nutrition-based food education using local resources. The integration of aquaculture into this area is considered strategic for strengthening the promotion of fish consumption and community food education. This activity aimed to develop an integrated aquaculture edu-tourism facility based on a recreational fishing pond at Undana Farm and to improve community understanding of the importance of fish consumption in supporting food security and stunting prevention. The implementation methods included a site survey, stocking tilapia fingerlings as a recreational and educational facility, and socialization on the benefits of fish consumption for visitors and the surrounding community. The activity involved the management of Undana Farm and 30 community participants as target partners. The results showed that Undana Farm has strong potential for the development of aquaculture edu-tourism in dryland areas. Stocking tilapia supported the availability of a fishing pond as both a recreational attraction and an educational medium. The socialization activities increased community participation and strengthened visitors’ understanding of the benefits of fish as a nutritious source of animal protein. The integration of agriculture and aquaculture also added value to the function of Undana Farm as an educational agro-tourism center that supports practical, participatory, and sustainable community learning. Therefore, integrated aquaculture edu-tourism is effective as a medium for fish consumption education and strengthening community food security, and it has the potential to be replicated in other dryland areas.